2013
DOI: 10.5093/tr2013a4
|View full text |Cite
|
Sign up to set email alerts
|

Incremental validity of proactive personality over the Big Five for predicting job performance of software engineers in an innovative context

Abstract: This study examined the incremental validity of proactive personality for predicting overall job performance over the Big Five in the context of an innovative software engineering job. Proactive personality and the Big Five were measured in a sample of 243 engineers and overall job performance was assessed through supervisor ratings in a sub-sample of 95 of these engineers. Results showed that even though proactive personality represents a valid and important predictor of performance it does not show a relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
(79 reference statements)
3
16
1
1
Order By: Relevance
“…Proactive Personality and the Big Five were measured in a sample of 243 engineers and overall job performance was assessed through supervisor ratings in a sub-sample of 95 of these engineers. Results showed that even though proactive personality represents a valid and important predictor of performance it does not show a relevant increment on the prediction yielded by extraversion, openness, conscientiousness, emotional stability and organizational tenure (Rodrigues and Rebelo, 2013).…”
Section: Impact Of Big Five Personality On Job Satisfactionmentioning
confidence: 97%
“…Proactive Personality and the Big Five were measured in a sample of 243 engineers and overall job performance was assessed through supervisor ratings in a sub-sample of 95 of these engineers. Results showed that even though proactive personality represents a valid and important predictor of performance it does not show a relevant increment on the prediction yielded by extraversion, openness, conscientiousness, emotional stability and organizational tenure (Rodrigues and Rebelo, 2013).…”
Section: Impact Of Big Five Personality On Job Satisfactionmentioning
confidence: 97%
“…In our study, we aim to observe extroversion at the assessed teams. On the contrary, Rodrigues and Rebelo [29] claimed that there is no connection between big five personality traits and team performance. Baumgart et al [20] found that agreeableness is the most important factor for the Developers when they investigated the important personality factors of the different roles in Scrum teams for a successful team performance.…”
Section: Personality Research In Software Engineeringmentioning
confidence: 99%
“…Among the publications on this subject, there is a trend towards the investigation of the individual performance background, focusing on features such as reasoning, personality, perception of leadership styles, participation in decision-making, job involvement, creativity and commitment (Coelho, 2009). Although this trend refl ects a view that there are innate characteristics that would lead to better performance (Meyers et al, 2013), some researchers suggest that acquired or developed characteristics and contextual aspects would also result in competent performances (Meyers et al, 2013;Oliveira et al, 2013;Rodrigues & Rebelo, 2013). Examples of these characteristics are leadership skills, performance, knowledge and values (Oliveira et al, 2013).…”
mentioning
confidence: 99%